1985
DOI: 10.1056/nejm198505093121902
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Plasma Lipids, Lipoproteins, and Apoproteins by Dietary Fish Oils in Patients with Hypertriglyceridemia

Abstract: Dietary fish oils, which are rich in omega-3 fatty acids, have been reported to reduce plasma lipid levels in normolipidemic subjects. We examined the effects of fish oil in 20 hypertriglyceridemic patients: 10 with Type IIb hyperlipidemia and 10 with Type V. These patients were put on three diets differing primarily in fatty acid composition and fat content. The control diet contained a fatty acid mixture typical of a low-fat therapeutic diet (ratio of polyunsaturated to saturated fat, 1.4), the fish-oil diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
112
3
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 792 publications
(127 citation statements)
references
References 18 publications
8
112
3
1
Order By: Relevance
“…Many studies have shown that feeding fish oil decreases the serum level of TG, and the mechanism of TG-lowering by fish oil appears to involve inhibition of VLDL secretion and TG synthesis. 1,4,23,24) The mechanisms governing n-3 fatty acid-mediated changes in lipid metabolism are thought to be partially mediated by the enhancement of peroxisome proliferator-activated receptor (PPAR) a. 25) Manipulation of the fatty acid composition of hepatic lipids by the feeding of fish oil has been shown to induce peroxisomal b-oxidation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have shown that feeding fish oil decreases the serum level of TG, and the mechanism of TG-lowering by fish oil appears to involve inhibition of VLDL secretion and TG synthesis. 1,4,23,24) The mechanisms governing n-3 fatty acid-mediated changes in lipid metabolism are thought to be partially mediated by the enhancement of peroxisome proliferator-activated receptor (PPAR) a. 25) Manipulation of the fatty acid composition of hepatic lipids by the feeding of fish oil has been shown to induce peroxisomal b-oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…4,5) The hypotriglyceridemic effect of fish oils has been recognized in humans as well as animals of different species. [6][7][8] The component in fish oil responsible for lowering TG is considered to be principally EPA, not DHA.…”
mentioning
confidence: 99%
“…Unsaturated fatty acids induce peroxisomal proliferation and lower blood triglyceride levels (1)(2)(3). Similar effects are evoked by a number of man-made compounds which are either considered for therapy of hyperlipidemia-e.g., clofibric acid, nafenopin, WY-14,643, or sulfur-substituted fatty acids-or are in use as industrial plasticizers (4)(5)(6).…”
mentioning
confidence: 94%
“…Dietary polyunsaturated fatty acids (PUFA), 1 particularly highly unsaturated n Ϫ 3 PUFA, have a strong suppressive effect on hepatic lipogenesis and triglyceride synthesis leading to a decline in plasma triglycerides (1)(2)(3)(4)(5)(6)(7). The suppression of hepatic lipogenesis is due, at least in part, to an inhibition of transcription of several genes encoding proteins involved in both lipogenesis and glycolysis, including fatty acid synthase, stearoyl-CoA desaturase, L-type pyruvate kinase, and the S14 protein (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%
“…The suppression of hepatic lipogenesis is due, at least in part, to an inhibition of transcription of several genes encoding proteins involved in both lipogenesis and glycolysis, including fatty acid synthase, stearoyl-CoA desaturase, L-type pyruvate kinase, and the S14 protein (1)(2)(3)(4)(5)(6)(7)(8)(9).…”
mentioning
confidence: 99%